2023
DOI: 10.3389/fphys.2023.1120341
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus tractus solitarii is required for the development and maintenance of phrenic and sympathetic long-term facilitation after acute intermittent hypoxia

Abstract: Exposure to acute intermittent hypoxia (AIH) induces prolonged increases (long term facilitation, LTF) in phrenic and sympathetic nerve activity (PhrNA, SNA) under basal conditions, and enhanced respiratory and sympathetic responses to hypoxia. The mechanisms and neurocircuitry involved are not fully defined. We tested the hypothesis that the nucleus tractus solitarii (nTS) is vital to augmentation of hypoxic responses and the initiation and maintenance of elevated phrenic (p) and splanchnic sympathetic (s) LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 98 publications
1
5
0
Order By: Relevance
“…These data support previous studies showing that PVN neurons appear to alter cardiorespiratory output without changes in sympathorespiratory coupling in a variety of circumstances, including acute intermittent hypoxia (Xing & Pilowsky, 2010), dehydration (Holbein et al, 2014), increased osmolality (Holbein & Toney, 2015) and hypertension (Holbein et al, 2018). These data further indicate that although the nTS plays a role in sympathorespiratory coupling (Molkov et al, 2014;Ostrowski et al, 2023), this coupling likely utilizes mechanisms other than those mediated by projections from the PVN to the nTS. Thus, the PVN-nTS pathway enhances cardiorespiratory responses to hypoxia without altering sympathorespiratory coupling, as does the PVN globally.…”
Section: Stimulation Of the Pvn-nts Projection Facilitates Nts Activa...supporting
confidence: 88%
See 3 more Smart Citations
“…These data support previous studies showing that PVN neurons appear to alter cardiorespiratory output without changes in sympathorespiratory coupling in a variety of circumstances, including acute intermittent hypoxia (Xing & Pilowsky, 2010), dehydration (Holbein et al, 2014), increased osmolality (Holbein & Toney, 2015) and hypertension (Holbein et al, 2018). These data further indicate that although the nTS plays a role in sympathorespiratory coupling (Molkov et al, 2014;Ostrowski et al, 2023), this coupling likely utilizes mechanisms other than those mediated by projections from the PVN to the nTS. Thus, the PVN-nTS pathway enhances cardiorespiratory responses to hypoxia without altering sympathorespiratory coupling, as does the PVN globally.…”
Section: Stimulation Of the Pvn-nts Projection Facilitates Nts Activa...supporting
confidence: 88%
“…Coupling of sympathetic nervous system activity to respiration is necessary for overall cardiovascular function, likely indicates interactions among cardiovascular and respiratory neurons, and may be associated with cardiovascular disease (Molkov et al., 2014; Ostrowski et al., 2023). Manipulation of the PVN‐nTS projection influenced both sympathetic and phrenic nerve activity responses to hypoxia and possibly their coupling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in SA patients have shown persistent increases in sympathetic nerve activity (SNA) ( Maier et al, 2022 ), decreased renal plasma flow ( Kinebuchi et al, 2004 ), glomerular hyperfiltration ( Kinebuchi et al, 2004 ), increased activity of the renin angiotensin aldosterone system (RAAS) ( Di Murro et al, 2010 ; Zalucky et al, 2015 ), as well as systemic inflammation ( Unnikrishnan et al, 2015 ; Perrini et al, 2017 ; Orrù et al, 2020 ) and evidence of oxidative stress ( Orrù et al, 2020 ; Hu et al, 2022 ). Previous studies have shown that the chronic intermittent hypoxia (CIH) associated with SA results in tonic increases in afferent carotid body chemoreflex (CBC) activity ( Peng et al, 2003 ; Rey et al, 2004 ; Roy et al, 2018 ; Prabhakar et al, 2023 ) as well as changes in central chemoreflex sensitivity, both of which contribute to elevated efferent SNA ( Prabhakar et al, 2023 ; Ostrowski et al, 2023 ; Gilmartin et al, 2010 ; Huang et al, 2009 ; Marcus et al, 2010 ; Molkov et al, 2011 ). Acute activation of the CBC with hypoxia has previously been shown to increase renal SNA and decrease renal blood flow (RBF) in healthy animals ( Huang et al, 2009 ; Marcus et al, 2015 ; Pügge et al, 2016 ; Kious et al, 2022 ), an effect exacerbated by conditions with enhanced chemoreceptor sensitivity ( Huang et al, 2009 ; Marcus et al, 2015 ; Pügge et al, 2016 ; Kious et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%